Short-term stability of a small open economy with an indexed exchange rate - Ciftcioglu, S (Fondo Cultura Economica, 1997)
This paper attempts to analyse the short-run macroeconomic stability of a small, open economy operating under the policy rule of lagged indexation of nominal exchange rate to domestic price level. The basic economic structure of the underlying open economy models has been made more realistic by allowing price-level inertia on the supply side, and output inertia on the demand side of the economy. The simulation of analytical results have indicated that, in all types of disturbances examined, except in the case of domestic price-level disturbances, the choice of relatively higher degree of indexation worsens short-run instability of both output and price level of the small, open economy. In the case of domestic price-level disturbances, higher degree of indexation reduces short-run instability of output but only at the expense of worsened price instability.